Putri Lentui: Konsep Garapan Tari Interpretasi Cerita Rakyat Desa Ujan Mas Kabupaten Muara Enim - Agustina, Mellinia (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The title of the dance work created is "Putri Lentui", the creation of the dance work was inspired by a folk tale or legend from an area in Muara Enim Regency, more precisely in Ujan Mas District. The creation of a dance work cannot be separated from the underlying concept. The choreographer creates a dance work through various work processes that are carried out, the first stage carried out is the search for ideas or concepts, namely the choreographer first seeks information about the folk tale that will become a concept for the dance work. From the results of the search for ideas or concepts that have been carried out, it becomes the main foundation for the choreographer to create a dance work. The concept of dance work is a framework or parts in creating a work that is composed of ideas or concepts, themes, titles, movements, dancers, make-up and costumes, stage layout, floor patterns, dance accompaniment, properties, and lighting. The methods used in creating the dance work Putri Lentui are exploration, improvisation, formation, and evaluation. The choreographer tries to explore, improvise, form, then evaluate from the ideas that have been obtained from exploring information about folklore in a region into a dance work. This dance work is based on a legendary story in Ujan Mas Village by strengthening the theme of feminism taken from the story of a princess named Putri Lentui. In this writing, the aim is to achieve the result that the basis of a story can be developed into a dance work by applying descriptive aspects in the process of working on it clearly, sequentially, and orderly.